Biogeochemistry of selenium. A review - Sharma, Virender K; McDonald, Thomas J; Sohn, Mary; Anquandah, George A. K; Pettine, Maurizio; Zboril, Radek (Environmental chemistry letters, 2015)
Selenium levels and speciation in environmental compartments and the dynamics of global Se cycling continue to be a subject of intense interest largely because Se is both an essential element and a toxicant at elevated levels. While Se containing amino acids and proteins are known to be critical for normal metabolic functions in many life forms, selenosis, poisoning due to chronic excessive Se intake, has been associated with neurological impairment. This paper reviews the current understanding of the biogeochemistry of selenium in the natural environment. The factors that affect Se speciation in natural environments are chemical, physical, and biological processes. Several inorganic species of Se (−2, 0, +4, and +6) and organic species (monomethylated and dimethylated) have been reported in aquatic systems. Both HSeO₃⁻and SeO₃²⁻would be present in natural waters. Under mild oxidizing conditions, HSeO₃⁻and SeO₃²⁻are the major species, while HSe⁻would be the dominant species at pH greater than 4 and strong reducing conditions. The biogeochemistry of selenium is discussed in terms of variation of speciation with pH and redox conditions, sorption on solid surfaces, role of reducing species under oxic/anoxic conditions, and interaction with natural organic matter.